The Impact of Product Quality on Customer Satisfaction at Cakue Supiah Medan - Haryanto, Cuan; Anggraini, Dewi (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2024)
Cakue Supiah Medan is a shop engaged in selling food with a specialization in selling cakes. The purpose of this study was to determine the effect of product quality on customer satisfaction at Cakue Supiah Medan. The research method used by the author in this study is a quantitative method, which is a type of research whose specifications are systematic, planned and clearly structured from the start to the creation of the research design. The number of populations in this study is unknown so to find samples using the Lemeshow formula and get 97 respondents. From the results of the coefficient of determination, it can be seen that the value of R Square (R2) or the coefficient of determination obtained is 0.486, meaning that the Customer Satisfaction variable can be explained by the Product Quality variable of 48.6% while the the remaining 51.4% is influenced by other factors that come from outside the model of this research such as service quality and price. The results of testing the hypothesis partially by using the t-test, it is known that the Product Quality variable has a value of tcount (5.425) > ttable (2.048) with a significant level of 0.000 <0.05 so it can be concluded that there is a partially significant positive effect between Product Quality on Customer satisfaction.